2017
DOI: 10.1007/s11517-017-1738-3
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc degeneration: an experimental and numerical study using a rabbit model

Abstract: Animal models have been extensively used for the study of degenerative diseases and evaluation of new therapies to stop or even reverse the disease progression. The aim of this study is to reproduce lumbar intervertebral disc degeneration in a rabbit model by performing a percutaneous annular puncture at L4L5 level. The effect of this damage on the spine behaviour was analysed combining three different techniques: imaging processing, mechanical testing and computational modelling. Twenty New Zealand white rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The peel test in the current study aims to quantify the tensile strain in the ILM when resisting delamination (Gregory et al, 2012). A limited number of studies have reported adhesion strength and variability in the AF including in the bovine tail (Harvey-Burgess and Gregory, 2019), rabbit (Gregory et al, 2014), porcine (Snow et al, 2018;Ghelani et al, 2020;McMorran and Gregory, 2021), and human (Calvo-Echenique et al, 2018) IVD. The peel strength values reported in the current study are similar to those reported previously in the bovine tail and porcine; while the reported values in the rabbit and human IVD were much lower (less than 1.0N/mm); however this may be a result of the high degree of degeneration in those experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peel test in the current study aims to quantify the tensile strain in the ILM when resisting delamination (Gregory et al, 2012). A limited number of studies have reported adhesion strength and variability in the AF including in the bovine tail (Harvey-Burgess and Gregory, 2019), rabbit (Gregory et al, 2014), porcine (Snow et al, 2018;Ghelani et al, 2020;McMorran and Gregory, 2021), and human (Calvo-Echenique et al, 2018) IVD. The peel strength values reported in the current study are similar to those reported previously in the bovine tail and porcine; while the reported values in the rabbit and human IVD were much lower (less than 1.0N/mm); however this may be a result of the high degree of degeneration in those experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, defects in adhesion of various non-biological composites have been shown to result in variability in the adhesion strength ( Rodríguez-Ramos et al, 2013 ). Similarly, a weakened and/or compromised AF may also increase the variability of adhesion strength which could in turn increase the possibility of circumferential tearing that can lead to IVD herniation, spinal nerve root compression, and a significant state of degeneration and pain in the spine ( Iyer and Kim, 2016 ; Calvo-Echenique et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors such as the inflammatory environment [ 4 , 5 ], autoimmunity [ 6 , 7 ], autophagy [ 8 ], fibrosis [ 9 ], and mechanical load [ 10 ] affect and mediate IVDD progression. Under the persistent influence of pathological mechanisms, NP cell extracellular matrix (ECM) causes degenerative phenotypic changes, including secretion of matrix metalloproteinases (MMPs) [ 11 ], various inflammatory mediators [ 12 ], and degeneration of aggrecan (Acan) and type II collagen (Col2a1) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-rodent animal models for IVD include rabbits, which display a similar disc morphology to humans and have been used to study degeneration as well as potential therapeutics ( Kroeber et al, 2002 ; Liu et al, 2011 ; Calvo-Echenique et al, 2018 ). Multiple larger animal models have also been established including canine, ovine, caprine, camelid, and porcine models ( Reid et al, 2002 ; Yoon et al, 2008 ; Bergknut et al, 2012 ; Stolworthy et al, 2015 ; Gullbrand et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%